Chemical Composition of Endemic Inula macrocephala Boiss. and Kotschy ex Boiss. from Turkey - Kilic, Omer; Bagci, Eyup (Asian Journal of Chemistry, 2013)
The essential oil components of aerial parts of Inula macrocephala Boiss. and Kotschy ex Boiss. was investigated by GC and GC-MS. The yield of oil is ca. 0.13 mL/100 g. Thirty five components were identified representing 90.7 % oil. Borneol (26.4 %), beta-caryophyllene (15.3 %), p-cymene (10.2 %) and bornyl acetate (8.9 %) were identified major components of plant. The results were discussed in terms of natural products, renewable resources and chemotaxonomy.
Keywords: Inula; Essential oil; Borneol; beta-Caryophyllene